Navigating the Seaweed Biorefinery Value Chain Implications for a Seaweed Farmer - Wenäll, Tilda; Leufstedt, Alva (My University, 2023)
The food industry faces several issues as the demand increases with population growth, and current production is not sufficient to cover global nutrition needs. Blue foods could reduce the overall environmental pressure from food production since it requires significantly less fresh water and land use than terrestrial crops. Currently, oceans provide only 2% of global food production, highlighting the untapped potential of blue foods, including seaweed. To increase the use of seaweed in both food and non-food applications, it could be processed in biorefineries to produce a wide range of products. Nordic SeaFarm, a Swedish seaweed farmer, wishes to explore these possibilities. This thesis aims to investigate where, and how, Nordic SeaFarm could position itself in the emerging value chain of products from seaweed biorefineries. This will be accomplished through an exploration of the technical and organisational resources within the resource network, including an analysis of the necessary collaborations, and an examination of the current situation. An abductive approach was taken for this qualitative study, where seven interviews with European biorefineries were conducted. Furthermore, two interviews with food product developers were held as they are the next key actors in the food value chain. The study shows that the European seaweed industry faces several challenges that Nordic SeaFarm has to consider. These challenges include the scarcity of biomass, the premium price of European biomass, the ambiguity of the concept of sustainability, and the vast investments and costs associated with the development and operation of a biorefinery. While some believe that European seaweed cultivation will scale up as demand increases, the course of action for European biorefineries working with cultivated seaweed remains uncertain if it does not scale sufficiently or if large-scale offshore cultivation proves to be complicated. Findings from the interviews show that most biorefineries primarily focus on high-value compounds for the pharmaceutical and cosmetics industries, to ensure viable business cases. However, the interviews indicate that there might be untapped potential in the side streams, which could possibly be further developed into food products. Based on the findings from the interviews three potential roles a seaweed farmer can undertake in the upstream value chain were explored. These roles are as a contractor-based supplier of seaweed, a consolidator of seaweed, or as a member of a seaweed cooperative. In addition, the possibility of undertaking a downstream role as a coordinator of the valorisation of side stream for food production is also analysed. These were later problematised in terms of feasibility and chronology, leading up to the recommendation of a combination of contractor-based collaboration with biorefineries and research partnerships to secure potential customers and the company’s position in the value chain. The recommendation further includes testing and developing food products from the biorefinery side streams.
Keywords: Seaweed; biorefinery; resource network; network collaborations; value chain; business relationships; emerging industry